Pesticide mixtures in the Swedish streams: environmental risks, contributions of individual compounds and consequences of single-substance oriented risk mitigation - Gustavsson, Mikael B; Kreuger, Jenny; Bundschuh, Mirco; Backhaus, Thomas (PeerJ Preprints, 2017)
The paper presents the ecotoxicological assessment and environmental risk evaluation of complex pesticide mixtures occurring in freshwater ecosystems in southern Sweden. The evaluation is based on the data collected between 2002 and 2013 by the Swedish pesticide monitoring program and includes 1308 individual samples, detecting mixtures of up to 54 pesticides (modal=8). The environmental risk of 77% of the samples exceeded acceptable levels, based on an assessment using Concentration-Addition and Swedish Water Quality Objectives (WQO) for the individual pesticides. Algae were the most sensitive organism group. However, the analytical detection limits, especially for insecticides, are currently insufficient to analyze concentrations at or near their WQO’s. Thus, the risk of the analyzed pesticide mixtures to crustaceans and fish is currently systematically underestimated. Throughout the monitoring the risk associated with pesticide mixtures is often driven by only 1-3 compounds. However, the risk-drivers differ substantially between sites and samples, so that 83 of the 141 monitored pesticides need to be included in the assessment to account for 95% of the risk at all sites and years. Single-substance oriented risk mitigation measures that would ensure that each individual pesticide is present at 95% of its individual WQO at maximum, would also reduce the mixture risk, from a median risk quotient of 2.7 to a median risk quotient of 2.3. However, acceptable total risk levels would still be exceeded in more than 70% of the samples.
Keywords: Kaplan-Meier method; mixture risk assessment; concentration addition; maximum cumulative ratio; chemical monitoring; mixture risk management